2016
DOI: 10.1101/gad.284604.116
|View full text |Cite
|
Sign up to set email alerts
|

A conserved virus-induced cytoplasmic TRAMP-like complex recruits the exosome to target viral RNA for degradation

Abstract: RNA degradation is tightly regulated to selectively target aberrant RNAs, including viral RNA, but this regulation is incompletely understood. Through RNAi screening in Drosophila cells, we identified the 3 ′ -to-5 ′ RNA exosome and two components of the exosome cofactor TRAMP (Trf4/5-Air1/2-Mtr4 polyadenylation) complex, dMtr4 and dZcchc7, as antiviral against a panel of RNA viruses. We extended our studies to human orthologs and found that the exosome as well as TRAMP components hMTR4 and hZCCHC7 are antivir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 84 publications
3
43
0
Order By: Relevance
“…The Trf-Air-Mtr4 polyadenylation (TRAMP) complex is a set of cofactors that prepares RNA substrates for degradation by the nuclear RNA exosome (see below; Table 1; LaCava et al 2005;Wyers et al 2005); however, this complex was recently shown to participate in viral defense in the cytoplasm (Molleston et al 2016). Infection of human and Drosophila cells with the disparate RNA viruses vesicular stomatitis virus, Sindbis virus, or Rift Valley fever virus (RVFV) was potentiated by knockdown of exosome and TRAMP components.…”
Section: Viral Defensementioning
confidence: 99%
“…The Trf-Air-Mtr4 polyadenylation (TRAMP) complex is a set of cofactors that prepares RNA substrates for degradation by the nuclear RNA exosome (see below; Table 1; LaCava et al 2005;Wyers et al 2005); however, this complex was recently shown to participate in viral defense in the cytoplasm (Molleston et al 2016). Infection of human and Drosophila cells with the disparate RNA viruses vesicular stomatitis virus, Sindbis virus, or Rift Valley fever virus (RVFV) was potentiated by knockdown of exosome and TRAMP components.…”
Section: Viral Defensementioning
confidence: 99%
“…The Drosophila-specific pathogen DCV was also often included in the screens because it could serve as a model for pathogenic enterovirus infections in mammals [110], while other Drosophila-(Nora virus) or insect-specific viruses (FHV) were rarely included. Besides genome-wide screens, also targeted screens were performed, for instance targeting specific signaling pathways, immune genes, RNA helicases, RNA metabolism and endoplasmic reticulum (ER)-associated proteins [99,[111][112][113][114].…”
Section: Identification Of Host Factors That Restrict Viral Infectionmentioning
confidence: 99%
“…Furthermore, it was regularly observed that host factors in Drosophila cells were conserved in mammalian (human) cells [112][113][114][117][118][119][120]. The results of the screens with respect to the (validated) identification of both new resistance mechanisms (VRFs, "antiviral genes") as well as (often virus-specific) cellular processes that are limiting to viral infection (VSFs, "proviral genes") are summarized in Table 1.…”
Section: Identification Of Host Factors That Restrict Viral Infectionmentioning
confidence: 99%
See 2 more Smart Citations